Case report: Upper gastrointestinal bleeding associated with pancreatic segmental portal hypertension: six case reports and literature review - Miao, Qian; Zheng, Zhongqing; Piao, Meiyu; Cao, Hailong; Wang, Bangmao; Liu, Wentian (Frontiers in Medicine, 2025)
BackgroundPancreatic segmental portal hypertension (PSPH) is a clinical syndrome in which splenic vein hypertension is caused by obstruction, stenosis, or thrombosis of the splenic veins in the primary pancreatic disease. Gastrointestinal hemorrhage caused by gastric varices (GVs) is one of the life-threatening complications in the patients with left portal hypertension. The aim was to report our experience and discuss the manifestations, management, and prognosis of PSPH with upper gastrointestinal bleeding (UGIB).MethodWe retrospectively analyzed six patients with PSPH and UGIB in our department. The clinical data were collected such as demographic information, medical history, and clinical presentation.ResultThe autoimmune pancreatitis, pancreatic tumor, pancreatic surgery, chronic pancreatitis and pancreatic pseudocyst were diagnosed in six patients, respectively. Five patients presented with hematemesis and/or melena on admission, and one patient presented with fatigue. All patients had isolated GVs. Follow-up patients were treated with portal vein stenting in one case, laparoscopic splenectomy in two cases, endoscopic gastric fundic vein embolization and injection of Cyanoacrylate Glue in one case, and improvement in conservative treatment in two cases. All patients were alive at the last follow-up.ConclusionPSPH should be seriously considered in patients with pancreatic disease with isolated GVs. It is particularly important to choose specific approaches for individual cases based on the primary disease, the severity of varicose veins and the general condition of the patients.